In Perfect Harmony : Bild + Rahmen 1850-1920. - Becker, Edwin; Cahn, Isabelle; Kemp, Wolfgang; Mendgen, Eva; Roberts, Lynn; Schröder, Klaus Albrecht; Traber, Christine; Waschek, Matthias; de Leeuw, Ronald; van Tilborgh, Louis; Van Gogh Museum, Amsterdam; Kunstforum Wien (Zwolle : Waanders Uitgevers, 1995)
Alma-Tadema, Lawrence ; Amiet, Cuno ; Balla, Giacomo ; Bellini, Giovanni ; Brown, Ford Madox ; Burne-Jones, Edward ; Böcklin, Arnold ; Choffard, P.P. ; Collins, Charles Allston ; Dali, Salvador ; Degas, Edgar ; Delacroix, Eugène ; Delaunay, Robert ; Doré, Gustave ; Duval, Victor ; Ernst, Max ; Fantin-Latour, Henri ; Feuerbach, Anselm ; Finch, Alfred William ; Friedrich, Caspar David ; Grandville ; Hofmann, Ludwig von ; Hughes, Arthur ; Hunt, William Holman ; Huszar, Vilmos ; Kandinsky, Wassily ; Khnopff, Fernand ; Kirchner, Ernst Ludwig ; Klimt, Gustav ; Klinger, Max ; Leighton, Frederic Lord ; Lemmen, Georges ; Lenbach, Franz von ; Magritte, René ; Makart, Hans ; Marées, Hans von ; Miro, Joan ; Mondriaan, Piet ; Moore, Albert Joseph ; Moreau, Gustave ; Munch, Edvard ; Nolde, Emil ; Picabia, Francis ; Picasso, Pablo ; Pissarro, Camille ; Puvis de Chavannes, Pierre ; Raffaëlli, Jean-François ; Redon, Odilon ; Rossetti, Dante Gabriel ; Schadow, Wilhelm von ; Schick, Rudolf ; Schlemmer, Oskar ; Schlobach, Willy ; Segal, Arthur ; Seurat, Georges ; Signac, Paul ; Stuck, Franz von ; Toorop, Jan ; Van Rysselberghe, Theo ; Waldmüller, Ferdinand ; Whistler, James Abbott McNeill ; de Toulouse-Lautrec, Henri ; de Velde, Henry Van ; van Doesburg, Theo ; van Gogh, Vincent
biografie
In Perfect Harmony : Bild + Rahmen 1850-1920, Van Gogh Museum, Amsterdam, 31. März - 25. Juni 1993, Kunstforum Wien, 24. August - 19. November 1993
Duits
boek